Themersonowie i ich późne dzieci. Słowografia w książkach dla młodych (i trochę starszych) „widzoczytelników” - Śniecikowska, Beata ((Dy)fuzje: Związki literatury i sztuki w Polsce po 1945 roku, 2019)
The article deals with wordgraphy in the Polish book art for children (compositions employing equally important words and images). The starting point of the study is the analysis of the books created in the 1930s by a couple of avant-garde artists, Franciszka and Stefan Themerson. It was only the last two decades that have seen a creative continuation of the verbo-visual concepts and artistic intuitions of the pair. In the second part of the article the author analyses different wordgraphic compositions by contemporary writers and illustrators: Iwona Chmielewska, Aleksandra (Machowiak) Mizielińska and Daniel Mizieliński, Ola (Aleksandra) Cieślak, Grażka (Grażyna) Lange.